Transformational Leadership as a Catalyst for Entrepreneurial Success: An Evidence from Empirical Research - Sukhadeve, Varsha S.; Tarar, Ashish Manohar (SEDME (Small Enterprises Development, Management & Extension Journal), 2024)
PurposeThis study explores how transformational leadership affects entrepreneurial success and identifies key mechanisms.OriginalityIt bridges the gap between existing literature on transformational leadership and entrepreneurial success by providing empirical insights.MethodologyA mixed-methods approach using surveys and case studies from 100 entrepreneurs, analysed with structural equation modelling (SEM) and interviews.Future ScopeFuture research could assess the long-term effects of transformational leadership on entrepreneurial success and explore moderating factors like industry type and cultural context.ImplicationsFindings show transformational leadership enhances entrepreneurial success through innovation and motivation, highlighting its importance for business growth. It suggests incorporating these skills into entrepreneurship programmes.ConclusionTransformational leadership is vital for entrepreneurial success, aiding in navigating challenges and achieving sustainable growth.
Keywords: Entrepreneurial Success; Innovation; Intellectual Stimulation; Leadership Communication; Transformational Leadership; Entrepreneurship